Analisis Efektivitas Implementasi Kebijakan Deep Learning di Sekolah - Tri Ariqoh Kholisah; Hamnah Rofiqoh; Aesha Najwa Alia; Bevan Multazam Pramudito; Suhardi Suhardi (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the effectiveness of implementing a deep learning approach in educational policy in Indonesia, specifically at the elementary school level. Using descriptive qualitative methods and literature study, this research reviews various scientific sources and educational policies from the last five years. The results indicate that deep learning has great potential in improving the quality of learning through three main components: meaningful learning, mindful learning, and joyful learning. These three aspects positively impact students' cognitive, affective, and social engagement. Data from schools implementing the School Driving program indicate significant improvements in students' critical thinking, collaborative skills, and motivation to learn. However, the effectiveness of the policy still faces challenges in the form of teacher readiness, infrastructure, and authentic learning assessment. Therefore, the success of deep learning implementation requires systemic support in the form of teacher training, integrated policies, and comprehensive evaluation instruments.